Heritage preservation in the post-digital era: How much information is enough?. Issue 1 (1st June 2021) - Thwaites, Harold
Digital media have revolutionized the practice of scholarship from archives to the creation of content. Continuing into the next decades, the application of digital technologies will remain a pivotal component to cultural heritage research-creation projects. Heritage preservation by means of virtual heritage or digital heritage broadly refers to the use and application of computational tools and methods to humanist fields of study. It embraces a transdisciplinary approach to inspire new research initiatives, while at the same time employing digital media technologies for content creation and sharing across the public space. This article provides an overview of the information design process applied to the digital preservation and re-presentation of cultural heritage. It employs principles of digital heritage to create a matrix of cultural heritage content within the themes of legacy, transmission and transformation. The intangible nature of world heritage is of increasing concern. How that can be preserved and how it becomes sampled and preserved in digital archives for the future are key questions, originating from the inquiry ‐ How much information is enough? This article endeavours to illuminate that question though an exemplar research-creation project, showcasing the materiality of the digital, its embodiment, agency and the resulting impact on the audiences it seeks to inform.